Pengembangan Naskah Storytelling Cerita Rakyat Timun Mas Pada Materi Perbandingan Dua Besaran SD Kelas V - Herdianti, Erika Rizki; Simanjuntak, Yolanda Helena; Nursyamsyiah, Nursyamsyiah; Safira, Rosida Naila; Melina, Shinta; Wiratomo, Yogi; Septiani , Eka (STKIP Taman Siswa Bima, 2024)
This research aims to improve the understanding of the children of SDIT Al-Muddatsiriyah of mathematical materials with ethnomatematics-based development of storytelling script in the 5th grade. This research is a development research focused on developing a story storytelling script based on people's stories on a two-dimensional comparison material. The development model used in this study is the development model of ADDIE which is: analysis stage (Analysis), design stage (Design), development stage (Development), implementation stage (Implementation), and evaluation stage. (Evaluation). But this study was not implemented due to the time limitation of the study and only conducted a small-scale trial on 5 students of V SD class. Data collection techniques use interviews, observations, and documentation. The data analysis techniques used are quantitative descriptive and qualitative. The results of the study showed that Storytelling scripts through the validation test of the experts – the mathematicians presented 98% and the presenting language experts 100% – then the storytelling script was said to be useful